2014
DOI: 10.32508/stdj.v17i1.1271
|View full text |Cite
|
Sign up to set email alerts
|

Changes of phenolic compounds of tea leaves during Oolong tea process

Abstract: It was believed that provided photographs of changes of total polyphenols (TPP), tannin, theaflavins (TF), thearubigins (TR) contents and total colour liquids. Green tea leaves were going through the stages: fresh tea → withering → incubated 1 → aromatic spin 1 → incubated 2 → aromatic spin 2 →fried inactivated enzymes. Tea samples in the stages were provided by Cau Tre tea factory. Tea samples were divided into two groups: the activated and inactivated enzyme groups – microwave was applied to treated the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Combined with the results of the metabolic pathway analysis, it was found that the contents of xanthine, 7-methylxanthine, 1,7-dimethylxanthine, theobromine, and 3-methylxanthine in the caffeine metabolism (Ko00232) pathway increased significantly after turning-over, indicating that the turning-over process is potentially beneficial to the synthesis of caffeine precursors. However, there were no significant changes in caffeine, which is in agreement with the previous conclusions that caffeine variation in oolong tea processing was not significant ( 48 , 49 ).…”
Section: Resultssupporting
confidence: 92%
“…Combined with the results of the metabolic pathway analysis, it was found that the contents of xanthine, 7-methylxanthine, 1,7-dimethylxanthine, theobromine, and 3-methylxanthine in the caffeine metabolism (Ko00232) pathway increased significantly after turning-over, indicating that the turning-over process is potentially beneficial to the synthesis of caffeine precursors. However, there were no significant changes in caffeine, which is in agreement with the previous conclusions that caffeine variation in oolong tea processing was not significant ( 48 , 49 ).…”
Section: Resultssupporting
confidence: 92%